Levulinic acid hydrogenation to γ-valerolactone over single Ru atoms on a TiO2@nitrogen doped carbon support. Issue 4 (10th February 2021) - Zhang, Kaili; Meng, Qinglei; Wu, Haihong; Yuan, Tongying; Han, Shitao; Zhai, Jianxin; Zheng, Bingxiao; Xu, Caiyun; Wu, Wei; He, Mingyuan; Han, Buxing
Abstract : TiO2 @nitrogen doped porous carbon dispersed single Ru atom catalyst (Ru/TiO2 @CN) efficiently transforms levulinic acid into γ-valerolactone at room temperature in water with a turnover frequency of 278 molGVL molRu −1 h −1 at complete conversion. Abstract : The transformation of levulinic acid (LA) into γ-valerolactone (GVL) in water at room temperature is very interesting. In this work, we designed and prepared single Ru atoms on a TiO2 @nitrogen doped porous carbon support catalyst (Ru/TiO2 @CN). It was demonstrated that the catalyst had very high activity, selectivity and stability for the conversion of LA into GVL at room temperature in water. The turnover frequency (TOF) could reach 278 molGVL molRu −1 h −1 at complete conversion, which was about 35 times higher than that of commercial Ru/C. In addition, only GVL was generated in the reaction over the catalyst of this work.